Tuberculin hypersensitivity hepatitis in mice infected with Mycobacterium bovis (BCG). - Ferluga, J. (1981)
A systemic BCG infection in mice induced multiple small granulomas located mainly in the periportal areas of the liver. Following systemic challenge of such mice with purified protein derivative of tuberculin (PPD), a rapidly developing hepatitis with diffuse intralobular mononuclear cell infiltration was precipitated, accompanied by high levels of aspartate transaminase in peripheral blood, hypoglycemia, focal hepatocyte necrosis, and accumulation of fibrinogen in liver. Bacterial lipopolysaccharide (LPS) also provoked acute hepatic damage both in BCG-infected mice and in mice pretreated with Corynebacterium parvum. PPD was not active in the latter. There were also lymphoid cell destruction and fibrinogen accumulation in the spleen of BCG-PPD-treated mice. Possible involvement of inflammatory and hepatotoxic mediators is suggested, and a T-lymphocyte-macrophage regulatory role in the pathogenesis of hepatitis is discussed.